1966
DOI: 10.4319/lo.1966.11.4.0499
|View full text |Cite
|
Sign up to set email alerts
|

Use of Artificial Substrata to Estimate the Productivity of Periphyton1

Abstract: Plexiglas plates were placed in laboratory streams and in a spring and removed at 2-to 4-day intervals to determine the increase in standing crop of periphyton.The instantaneous growth rate, calculated from the growth curve of periphyton on plates in the streams, was 0.51 g mea day-l as compared to an estimate of 0.60 g m-' day-' obtained by oxygen measurements for growth of periphyton on the stream bottom. The average growth rate of periphyton on plates in the streams over a single exposure period was 0.31 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 2 publications
(1 reference statement)
2
20
0
1
Order By: Relevance
“…Growth of periphytic bacteria and algae on mesocosm walls is typically rapid, reaching significant levels within 2 to 3 d (e.g. Kevern et al 1966, Kuiper 1981) and often dominating both biomass and productivity within relatively short (7 d) time periods (Chen 1998). Even for systems with periodic wall cleaning, rapidly growing periphyton can still alter metabolic processes in planktonic and benthic communities (Dudzik et al 1979, Chen 1998.…”
Section: Implications For Nutrient Cycling Experimentsmentioning
confidence: 99%
“…Growth of periphytic bacteria and algae on mesocosm walls is typically rapid, reaching significant levels within 2 to 3 d (e.g. Kevern et al 1966, Kuiper 1981) and often dominating both biomass and productivity within relatively short (7 d) time periods (Chen 1998). Even for systems with periodic wall cleaning, rapidly growing periphyton can still alter metabolic processes in planktonic and benthic communities (Dudzik et al 1979, Chen 1998.…”
Section: Implications For Nutrient Cycling Experimentsmentioning
confidence: 99%
“…McIntire and Phinney 1965;Eichenberger 1975) and on artificial substrates exposed to field conditions (e.g. Newcombe 1950;Sladecek and Sladeckova 1964;Kevern et al 1966) and various phases of algal growth have been identified. Similar patterns of colonization and growth of periphyton seem to occur on surfaces of submersed macrophytes.…”
mentioning
confidence: 99%
“…Sladecek and Sladeckova (1964) reviewed the different methods used for the analysis of production on artificial sub~ strate. The instantaneous biomass accumulation method (Kevern, et al 1966) provided a refinement of production estimates in that only the acceleration phase of periphyton growth is considered. Thus, estimates from.the instantaneous biomass accumulation method are higher.…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%